From Symptoms to Solutions: A Homeopathic Perspective on Chronic Bronchitis (Homoeopathy for All, 2025)
Chronic bronchitis (CB) is a common but variable phenomenon in Chronic Obstructive Pulmonary Disease (COPD). It has numerous clinical consequences, including an accelerated decline in lung function, greater risk of the development of airflow obstruction in smokers, a predisposition to lower respiratory tract infection, higher exacerbation frequency, and worse overall mortality. CB is caused by overproduction and hypersecretion of mucus by goblet cells, which leads to worsening airflow obstruction by luminal obstruction of small airways, epithelial remodeling, and alteration of airway surface tension predisposing to collapse.
Keywords: Mucus; Cell; Small; Collapse